#### Answer

$(f+g)(x)=2x^{2}+x-6$
$(f+g)(5)=49$

#### Work Step by Step

$(f+g)(x)=f(x)+g(x)$
$=x-6+2x^{2}$
$=2x^{2}+x-6$
Plug in $x=5$ into $2x^{2}+x-6$.
$(f+g)(5)=2\times5^{2}+5-6=2\times25-1=50-1=49$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$(f+g)(x)=2x^{2}+x-6$
$(f+g)(5)=49$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.